De Pulchritudine non est Disputandum? A cross‐cultural investigation of the alleged intersubjective validity of aesthetic judgment. (1st August 2018) - Cova, Florian; Olivola, Christopher Y.; Machery, Edouard; Stich, Stephen; Rose, David; Alai, Mario; Angelucci, Adriano; Berniūnas, Renatas; Buchtel, Emma E.; Chatterjee, Amita; Cheon, Hyundeuk; Cho, In‐Rae; et al.
Abstract : Since at least Hume and Kant, philosophers working on the nature of aesthetic judgment have generally agreed that common sense does not treat aesthetic judgments in the same way as typical expressions of subjective preferences—rather, it endows them with intersubjective validity, the property of being right or wrong regardless of disagreement. Moreover, this apparent intersubjective validity has been taken to constitute one of the main explananda for philosophical accounts of aesthetic judgment. But is it really the case that most people spontaneously treat aesthetic judgments as having intersubjective validity? In this paper, we report the results of a cross‐cultural study with over 2, 000 respondents spanning 19 countries. Despite significant geographical variations, these results suggest that most people do not treat their own aesthetic judgments as having intersubjective validity. We conclude by discussing the implications of our findings for theories of aesthetic judgment and the purpose of aesthetics in general.